1984
DOI: 10.1111/1523-1747.ep12260388
|View full text |Cite
|
Sign up to set email alerts
|

Skin Irritancy of Surfactants As Assessed by Water Vapor Loss Measurements

Abstract: A method to assess the irritancy of chemicals on human skin that is based on measurements of skin (water) vapor loss (SVL) is presented. The SVL measurements were performed with the Servo Med Evaporimeter in a group of 27 healthy volunteers. Four surfactants, distilled water, and NaCl 0.9% in distilled water were assayed. For the exposures a chamber technique was used. Sodium lauryl sulfate and cocobetaine most markedly influenced the loss of water through the skin. Polysorbate-60 and sodium laurate had less e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
1

Year Published

1991
1991
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(50 citation statements)
references
References 13 publications
1
48
1
Order By: Relevance
“…Consequently, it can be suggested that the application of a substance, which is able to perturb the skin barrier to a certain extent, does not directly trigger an irritation response. This seems contradictory to the common belief that TEWL measurements are a reliable method to assess the irritability of substances [21][22][23]. However, it is possible that this correlation is merely an exceptional case for certain classes of compounds, for which the degree of skin irritation is dependent on their degree of skin barrier perturbation.…”
Section: Correlation Between Tewl and Ldv Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…Consequently, it can be suggested that the application of a substance, which is able to perturb the skin barrier to a certain extent, does not directly trigger an irritation response. This seems contradictory to the common belief that TEWL measurements are a reliable method to assess the irritability of substances [21][22][23]. However, it is possible that this correlation is merely an exceptional case for certain classes of compounds, for which the degree of skin irritation is dependent on their degree of skin barrier perturbation.…”
Section: Correlation Between Tewl and Ldv Resultsmentioning
confidence: 81%
“…In this study we investigate irritation and enhancement effects after topical application of fatty acids to human skin using noninvasive bioengineering methods: transepidermal water loss (TEWL) and laser Doppler velocimetry (LDV). TEWL has been used in relation to the assessment of either the irritation [21][22][23] or the effects of penetration enhancers [15]. The correlation between these effects has not yet been fully established.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study human skin recombi nants made of human keratinocytes cultured on deepidermized dermis (RE-DED) or on fibroblast-populated collagen matrix (LSE™, Living Skin Equivalent) were used to study the irritating effect of sodium lauryl sulfate (SLS), a well-known and intensively studied primary contact chemical irritant [12][13][14], The extent of cytotoxicity induced after an exposure to SLS was evaluated on basis of (1) morphological perturbations, (2) changes in the expression of differentiation-specific pro tein markers (keratin 1, 10, 6, 16, involucrin and transglutaminase), (3) LDH release and (4) release of proinfiammatory mediators (PGE2, IL-l,IL-6,andIL-8). 50 Ponec/Kempenaar In vitro Testing of SLS Irritancy…”
Section: Introductionmentioning
confidence: 99%
“…were measured. The results were generally interpreted in terms of a modification of the barrier function of the stratum corneum and irritation phenomena [1][2][3][4].In vitro studies have been far less frequent, and only the swelling of the corneal layer [5], together with changes in its viscoelastic prop erties, were described and discussed in rela tion to various types of molecular arrange …”
mentioning
confidence: 99%